Epoxy anhydride composition capable of being chemically thickened and preparation method thereof
By introducing surfactant-modified nanoclays, graphene quantum dots (GQDs) and two-dimensional transition metal carbides/nitrides (MXene) into the epoxy anhydride composition, a complex multi-level structure is formed, which solves the problem of degradation in the performance of traditional resins in humid and heat environments, and improves high mechanical properties, thermal stability and electromagnetic shielding performance, which is suitable for the development of high-performance composite materials.
Patent Information
- Application Number
- CN202510060915.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-04
AI Technical Summary
The performance of traditional epoxy/acid anhydride wrapping resins in humid and heat environments is degraded, especially after humid and heat cycles, and its glass transition temperature is significantly reduced, resulting in weakening of material strength and unstable size. At the same time, the conductivity and electromagnetic shielding performance are limited, making it difficult to meet the needs of modern electronic equipment.
A chemically thickened epoxy anhydride composition consisting of epoxy resin, modified anhydride curing agent, chemical thickening agent, latent accelerator, toughener, surfactant modified nanoclay, graphene quantum dots (GQDs) and two-dimensional transition metal carbide/nitride (MXene). Through the synergistic action of these components, a complex multi-level structure is formed to improve the mechanical properties, thermal stability and electromagnetic shielding performance of the material.
The composition maintains excellent mechanical properties, thermal stability and electromagnetic shielding performance in complex environments, solves the problem of degradation of traditional resins in humid and hot environments, and significantly improves the conductivity and electromagnetic shielding performance. It is suitable for aerospace, automobile industry, and electronic equipment.
Smart Images

Figure CN119752116A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of resin materials, in particular to an epoxy anhydride composition capable of chemical thickening and a preparation method thereof. Background Art
[0002] In order to obtain higher working capacity, composite material structure design is adopted, especially for high-performance parts in the aerospace field. These parts not only need to have high strength and high modulus, but also need to maintain stable performance in extreme environments, such as high temperature, high humidity and rapid temperature changes. For example, some parts of aerospace systems must be able to withstand drastic temperature fluctuations, from normal temperature in the ground environment to extremely low temperature in the vacuum environment at high altitude, and then to long-term solar radiation heating after entering orbit. Therefore, extremely high requirements are placed on the moisture and heat resistance and dimensional stability of the material.
[0003] Although traditional epoxy / anhydride winding resins have good mechanical properties, they are prone to performance degradation in hot and humid environments, especially after undergoing hot and humid cycles, their glass transition temperature (Tg) is significantly reduced, resulting in weakened material strength and dimensional instability. In addition, the conductivity and electromagnetic shielding properties of traditional resins are also relatively limited, making it difficult to meet the requirements of modern electronic devices for anti-electromagnetic interference. In order to solve these problems, it is particularly important to develop a new epoxy anhydride composition. Summary of the invention
[0004] In view of the deficiencies in the prior art, the present invention provides a chemically thickened epoxy anhydride composition and a preparation method thereof, which can maintain excellent mechanical properties, thermal stability and electromagnetic shielding effectiveness in complex environments, thereby solving the problems of the above-mentioned background technology.
[0005] According to a first aspect of the present invention, there is provided a chemically thickened epoxy anhydride composition, comprising the following components in parts by weight:
[0006] Epoxy resin: 35-45 parts;
[0007] Modified anhydride curing agent: 40-55 parts;
[0008] Chemical thickener: 3-8 parts;
[0009] Latent promoter: 0.5-2 parts;
[0010] Toughening agent: 5-20 parts;
[0011] Surfactant-modified nanoclay: 0.5-5 parts;
[0012] Surfactant-modified graphene quantum dots (GQDs): 0.01-0.5 parts;
[0013] Surfactant-modified two-dimensional transition metal carbide / nitride (MXene): 0.1-1 part;
[0014] Thermoresponsive polymer: 0.1-2 parts;
[0015] Photoresponsive molecules: 0.05 to 1 part;
[0016] Nanoparticles: 0.5-3 parts;
[0017] High performance fiber: 0-10 parts;
[0018] Wherein, the modified anhydride curing agent comprises a compound having a structure of Formula 1:
[0019] R-(CO)n-(OCH2CH2)m-OH Formula 1
[0020] Wherein, R is a C3-C6 alkyl group or a branched alkyl group, n is an integer from 1 to 10, and m is an integer from 10 to 40.
[0021] The lamellar structure of nanoclay can act as a physical barrier to prevent crack propagation and improve the fracture toughness of the material. Its high specific surface area forms a strong interfacial interaction with the epoxy resin matrix, further increasing the strength of the material.
[0022] GQDs have extremely high Young's modulus and tensile strength. They are evenly dispersed in the matrix and can act as tiny reinforcing agents. At the same time, the rich functional groups on their surface help to form chemical bonds with epoxy resin and improve the overall mechanical properties.
[0023] MXene has extremely high Young's modulus and tensile strength, and its flaky structure can effectively disperse stress and prevent crack propagation.
[0024] When the three coexist, they can form a complex multi-layer structure in the matrix. Nanoclay provides basic sheet support, GQDs fill the gaps between nanoclay sheets, and MXene is embedded in the three-dimensional network composed of nanoclay and GQDs. This structure significantly enhances the rigidity and toughness of the material, improves its response to impact loads, and makes the material less prone to brittle fracture.
[0025] The high strength and good conductivity of MXene and GQDs provide additional stress transfer paths, making the external force more evenly distributed inside the material and reducing local stress concentration.
[0026] The synergistic effect of the three can improve the thermal stability and dimensional stability of the material. Nanoclay limits the movement of molecular segments, slows down the relaxation process of molecular chains at high temperatures, improves the thermal stability of the material, and reduces the linear expansion coefficient. GQDs promote the cross-linking density of epoxy resin, so that the cured product has a higher glass transition temperature (Tg), thereby maintaining the shape and dimensional stability of the material at higher temperatures. MXene has excellent thermal stability and low expansion coefficient, and maintains stable physical and chemical properties in high temperature environments.
[0027] MXene further restricts the movement of molecular chain segments and enhances the heat resistance of the material; the lamellar structure provided by nanoclay and the chemical bonding of GQDs work together to reduce the linear expansion coefficient of the material and reduce the volume shrinkage caused by temperature changes.
[0028] The combination of the three enables the composite material to exhibit better resistance to deformation when undergoing rapid heating or cooling cycles, enhances adaptability to rapid heating and cooling cycles, maintains good dimensional stability, and can enhance conductivity and electromagnetic shielding performance.
[0029] Although nanoclay itself is a non-conductive material, it can indirectly affect the conductive path of the material by adjusting the filler distribution, guiding other conductive fillers (such as carbon fibers) to form a continuous conductive grid.
[0030] GQDs are highly efficient conductive materials. Adding a small amount can significantly improve the conductivity of the material and give the material a certain electromagnetic shielding effect. MXene itself is a highly efficient conductive material with good electromagnetic wave absorption properties and can be used for electromagnetic shielding.
[0031] When MXene and GQDs are used together, the two can form a denser and continuous conductive path, greatly improving the conductivity and electromagnetic shielding effectiveness of the material. Nanoclay provides structural support to ensure that these conductive fillers are evenly distributed, avoid agglomeration, and ensure the best conductive effect.
[0032] The synergistic effect of MXene and GQDs not only improves the electrical conductivity of the material, but also enhances the absorption and reflection capabilities of electromagnetic waves, thereby significantly improving the electromagnetic shielding effectiveness.
[0033] Moreover, the combination of the three can improve the chemical corrosion resistance and oxidation resistance of the material. Nanoclay has good chemical inertness and can effectively prevent external harmful substances from penetrating into the interior of the material, playing a role in protecting the matrix. It can also absorb some free radicals and delay the aging process of the material.
[0034] The surface of GQDs contains a large number of unsaturated bonds and active sites, which can capture and neutralize free radicals and reduce the probability of oxidation reactions. In addition, GQDs can also produce synergistic reactions with other additives to further enhance the corrosion resistance of the material.
[0035] The surface of MXene contains abundant functional groups, which can adsorb and neutralize free radicals, slowing down the aging process of the material. At the same time, MXene can also act as a barrier to prevent external corrosive media from reaching the matrix.
[0036] The three work together to provide multiple protection mechanisms for the material. Nanoclay blocks external corrosive media, MXene captures free radicals, and GQDs strengthen the intermolecular forces in the local area. Together, the material maintains good stability and durability in harsh environments.
[0037] Surfactant modification of nanoclay, GQDs and MXene improves their dispersibility and compatibility in epoxy resin. Surfactants can prevent filler agglomeration and ensure that the components are evenly distributed in the matrix to maximize the synergistic effect. The modified fillers form stronger interfacial interactions with epoxy resin, improving the overall performance.
[0038] According to an embodiment of the present invention, the epoxy resin is selected from modified bisphenol A epoxy resin and modified bisphenol F epoxy resin, and the epoxy value is 0.400eq / 100g to 0.800eq / 100g;
[0039] According to an embodiment of the present invention, the modified anhydride curing agent is a mixture of tung oil anhydride and 2-methyltetrahydrophthalic anhydride, and the mass ratio of the tung oil anhydride to the 2-methyltetrahydrophthalic anhydride is 1:1 to 3:1.
[0040] According to an embodiment of the present invention, the chemical thickener is selected from one or more of polyamide, polyurethane, and silicone thickeners, and the chemical thickener can increase the viscosity of the composition to 3 to 5 times the initial viscosity at room temperature.
[0041] According to an embodiment of the present invention, the latent promoter is 2-ethyl-4-methylimidazole.
[0042] According to an embodiment of the present invention, the toughening agent is a carboxyl-terminated liquid nitrile rubber, and the toughening agent can significantly improve the toughness of the cured product without significantly reducing the glass transition temperature (Tg).
[0043] According to an embodiment of the present invention, the surfactant-modified nanoclay is nanoclay modified with a first surfactant;
[0044] Wherein, the first surfactant is one of cetyltrimethylammonium bromide (CTAB) and sodium dodecyl sulfate (SDS);
[0045] The average particle size of the nanoclay is 10 to 100 nanometers;
[0046] The nano clay is one or both of montmorillonite and bentonite.
[0047] According to an embodiment of the present invention, the nanoparticles are selected from one of titanium dioxide (TiO2) and aluminum oxide (Al2O3), which can further disperse stress and increase the overall strength and toughness of the material; nanoparticles such as titanium dioxide (TiO2), aluminum oxide (Al2O3), etc. are added to the premixed composition, and stirring is continued to ensure that it can further disperse stress and increase the overall strength and toughness of the material. The introduction of nano-scale metal oxide particles can be filled into the three-dimensional network composed of nanoclay, GQDs and MXene. Improved mechanical properties: Nanoparticles can further disperse stress and increase the overall strength and toughness of the material. The additional barrier provided by the nanoparticles can effectively block external erosion media and improve the chemical corrosion resistance of the material.
[0048] According to an embodiment of the present invention, the high-performance fiber is selected from one of aramid fiber and glass fiber, which can achieve reinforcement effects in different directions, so that the material has excellent mechanical properties in all dimensions. High-performance fibers, such as aramid fiber or glass fiber, are introduced to form a multi-level reinforcement system. The combination of multiple fibers can achieve reinforcement effects in different directions, so that the material has excellent mechanical properties in all dimensions. The use of lightweight but high-strength fibers can significantly improve material performance without adding too much weight. High-performance fibers such as aramid fiber, glass fiber, etc. are added to the premixed composition, and continued stirring is continued to ensure that it can achieve reinforcement effects in different directions, so that the material has excellent mechanical properties in all dimensions.
[0049] According to an embodiment of the present invention, the thermoresponsive polymer is selected from poly (N-isopropylacrylamide) (PNIPAM), which can undergo phase change at a specific temperature to improve the moisture and heat resistance and self-healing ability of the material; a temperature-responsive polymer, such as poly (N-isopropylacrylamide) (PNIPAM), is introduced. This polymer will undergo a phase change at a specific temperature, thereby changing the physical properties of the material. When the ambient temperature rises, PNIPAM will change from a hydrophilic state to a hydrophobic state, reducing water absorption and improving the moisture and heat resistance of the material. The phase change caused by temperature changes can help the material self-repair tiny cracks and extend its service life.
[0050] According to an embodiment of the present invention, the photoresponsive molecule is selected from one of azobenzene derivatives, which can undergo cis-trans isomerization under light, thereby optimizing the mechanical properties and electromagnetic shielding effectiveness of the material.
[0051] Adding photoresponsive molecules, such as azobenzene derivatives, will undergo cis-trans isomerization under light, changing the internal structure of the material. The mechanical properties and conductivity of the material can be adjusted by light, which is suitable for application scenarios that require dynamic adjustment of properties. Photoresponsive molecules can work together with MXene and GQDs to optimize the absorption and reflection characteristics of electromagnetic waves and improve electromagnetic shielding effectiveness.
[0052] According to an embodiment of the present invention, the surfactant-modified graphene quantum dots are graphene quantum dots modified with a second surfactant;
[0053] Wherein, the second surfactant is one of polyvinyl alcohol (PVA) and polyacrylic acid (PAA);
[0054] The size of the graphene quantum dots (GQDs) ranges from 1 to 10 nanometers.
[0055] The graphene quantum dots (GQDs) have good dispersibility and high specific surface area, and the GQDs can significantly improve the electrical conductivity and electromagnetic shielding effectiveness of the material.
[0056] According to an embodiment of the present invention, the surfactant-modified two-dimensional transition metal carbide / nitride (MXene) is a two-dimensional transition metal carbide / nitride modified with a third surfactant;
[0057] Wherein, the third surfactant is one or both of hexadecyltrimethylammonium chloride (CTAC) and octadecylamine;
[0058] The two-dimensional transition metal carbide / nitride (MXene) is one or more of transition metal carbides or nitrides such as Ti3C2Tx, V2CTx, and Nb2CTx. The MXene has excellent electrical conductivity and mechanical properties, and can significantly enhance the overall strength and toughness of the material.
[0059] According to a second aspect of the present invention, there is provided a method for preparing the above-mentioned epoxy anhydride composition, comprising the following steps:
[0060] Preparation of surfactant-modified two-dimensional transition metal carbides / nitrides, surfactant-modified graphene quantum dots, and surfactant-modified nanoclays;
[0061] The epoxy resin, modified anhydride curing agent, latent accelerator and toughening agent are mixed and stirred evenly to ensure that all ingredients are fully dispersed and evenly mixed. During the stirring process, the temperature is controlled at 20°C to 80°C, the stirring speed is 500r / min to 1500r / min, the pressure is 100Pa to 101.325kPa, and the time is 1 hour to 3 hours;
[0062] The mixed composition is subjected to vacuum degassing treatment to remove bubbles generated during the mixing process. The vacuum degassing treatment time is 30 minutes to 1 hour, and the vacuum degree is -99.5KPa;
[0063] Add the thermoresponsive polymer and the photoresponsive molecule to the premixed composition and continue stirring until uniform;
[0064] Add nanoparticles and high-performance fibers to the premixed composition and continue to stir evenly; add thermoresponsive polymers such as PNIPAM to the premixed composition and continue to stir evenly to ensure that it can undergo a phase change at a specific temperature to improve the material's moisture and heat resistance and self-healing ability.
[0065] Add photoresponsive molecules such as azobenzene derivatives to the premixed composition and continue to stir evenly to ensure that it can undergo cis-trans isomerization under light to optimize the mechanical properties and electromagnetic shielding effectiveness of the material.
[0066] Add the surfactant-treated nanoclay, GQDs, and MXene to the premixed composition and continue stirring to ensure that the ingredients are evenly distributed in the matrix.
[0067] According to an embodiment of the present invention, the preparation of surfactant-modified two-dimensional transition metal carbides / nitrides, surfactant-modified graphene quantum dots and surfactant-modified nanoclays comprises:
[0068] Preparation of the surfactant-modified nanoclay: dissolving a first surfactant in deionized water to prepare a first surfactant solution with a concentration of 0.5 to 2 wt %;
[0069] Adding nanoclay to the first surfactant solution to make the mass fraction of the nanoclay be 1 to 5 wt %, using ultrasound or stirring to fully disperse the nanoclay and make it completely contact with the surfactant, then washing and drying to obtain the surfactant-modified nanoclay;
[0070] According to an embodiment of the present invention, the surfactant-modified graphene quantum dots are prepared:
[0071] Dissolving the second surfactant in deionized water to prepare a second surfactant solution with a concentration of 1 to 3 wt %;
[0072] Dispersing graphene quantum dots into the second surfactant solution so that the mass fraction of the graphene quantum dots is 0.1 to 1 wt %;
[0073] Stirring at 60-80° C. for 1-2 hours to ensure that the surfactant molecules can be effectively adsorbed onto the surface of GQDs, washing and drying to obtain the surfactant-modified graphene quantum dots;
[0074] According to an embodiment of the present invention, a surfactant-modified two-dimensional transition metal carbide / nitride is prepared:
[0075] The third surfactant is dissolved in deionized water to prepare a third surfactant solution with a concentration of 0.5-2wt%; the two-dimensional transition metal carbide / nitride is dispersed in the third surfactant solution, and the mass fraction of the two-dimensional transition metal carbide / nitride is 0.5-2wt%.
[0076] The mixture is stirred at 60-80° C. for 1-2 hours to ensure that the surfactant molecules can be effectively adsorbed onto the surface of the MXene, and then washed and dried to obtain the surfactant-modified two-dimensional transition metal carbide / nitride.
[0077] According to an embodiment of the present invention, the preparation of the surfactant-modified nanoclay specifically includes:
[0078] Dissolving the first surfactant in deionized water to prepare a first surfactant solution with a concentration of 0.5 to 2 wt %;
[0079] Adding nanoclay to the first surfactant solution so that the mass fraction of the nanoclay is 1 to 5 wt %;
[0080] Using a high-speed stirrer to stir at a speed of 1000-2000 rpm for 30 minutes, followed by ultrasonic treatment for 30-60 minutes to ensure that the nanoclay is fully dispersed and in full contact with the surfactant;
[0081] The treated suspension is centrifuged (speed 4000-8000 rpm, time 10-20 minutes), and the supernatant is removed;
[0082] The precipitate was washed several times with deionized water or ethanol to remove the unadsorbed surfactant;
[0083] The washed nanoclay is dried in a vacuum drying oven at 60° C. for more than 12 hours until it is completely dried to obtain the surfactant-modified nanoclay.
[0084] According to an embodiment of the present invention, preparing the surfactant-modified graphene quantum dots specifically includes:
[0085] Dissolving the second surfactant in deionized water to prepare a second surfactant solution with a concentration of 1 to 3 wt %;
[0086] The graphene quantum dots are dispersed in the second surfactant solution so that the mass fraction of the graphene quantum dots is 0.1 to 1 wt %.
[0087] Stir at room temperature for 2 to 4 hours, or under mild heating conditions (no more than 80 ° C) for 1 to 2 hours to ensure that the surfactant molecules can be effectively adsorbed to the surface of GQDs;
[0088] The treated suspension is centrifuged (rotation speed 8000-12000 rpm, time 10-20 minutes), and the supernatant is removed.
[0089] The precipitate was washed several times with deionized water or ethanol to remove the unadsorbed surfactant;
[0090] The washed GQDs were dried in a vacuum oven at 60 °C for more than 12 h until completely dry.
[0091] The dried GQDs should be stored in a dry environment to avoid moisture, thereby obtaining the surfactant-modified graphene quantum dots.
[0092] According to an embodiment of the present invention, preparing a surfactant-modified two-dimensional transition metal carbide / nitride specifically includes:
[0093] The third surfactant is dissolved in deionized water to prepare a third surfactant solution with a concentration of 0.5-2wt%; the two-dimensional transition metal carbide / nitride is dispersed in the third surfactant solution, and the mass fraction of the two-dimensional transition metal carbide / nitride is 0.5-2wt%.
[0094] Stir at room temperature for 2 to 4 hours, or under mild heating conditions (no more than 80 ° C) for 1 to 2 hours to ensure that the surfactant molecules can be effectively adsorbed to the MXene surface;
[0095] The treated suspension is centrifuged (rotation speed 8000-12000 rpm, time 10-20 minutes), and the supernatant is removed;
[0096] The precipitate was washed several times with deionized water or ethanol to remove the unadsorbed surfactant;
[0097] The washed MXene was dried in a vacuum drying oven at 60 °C for more than 12 h until it was completely dry.
[0098] The dried MXene should be stored in a dry environment to avoid moisture, thereby obtaining the surfactant-modified two-dimensional transition metal carbide / nitride.
[0099] The application of the epoxy anhydride composition provided by the present invention in preparing a composite material can be:
[0100] Winding the composition into a carbon fiber composite material;
[0101] Special equipment parts are formed through a medium-temperature curing process, wherein the medium-temperature curing process is: first, curing at 80°C for 4 to 6 hours; then curing at 110°C for 2 to 4 hours; and finally curing at 40°C for 2 to 4 hours. Preferably, the composite material formed after curing has high strength, high modulus and good toughness, and a high glass transition temperature (Tg), which can meet special use requirements.
[0102] The carbon fiber composite material is suitable for the fields of aerospace, automobile industry, electronic equipment, etc., especially for the occasions requiring high strength, heat and moisture resistance and electromagnetic shielding performance.
[0103] After the carbon fiber composite material is cured at medium temperature, its tensile strength is not less than 100 MPa, its tensile modulus is not less than 10 GPa, its elongation at break is not less than 3%, and its glass transition temperature (Tg) is higher than 150°C.
[0104] The present invention provides a chemically thickened epoxy anhydride composition and a preparation method thereof. The novel epoxy anhydride composition provided by the present invention significantly improves the moisture and heat resistance and dimensional stability of the material by introducing nanoclay, graphene quantum dots (GQDs) and two-dimensional transition metal carbides / nitrides (MXene), so that it can maintain excellent mechanical properties and thermal stability in extreme environments. The combination of the three makes the composite material show better deformation resistance under the condition of rapid heating or cooling cycles, enhances the adaptability of rapid heating and cooling cycles, maintains good dimensional stability, and can enhance electrical conductivity and electromagnetic shielding performance. It can be applied to the aerospace field.
[0105] The synergistic effect of nanoclay, GQDs and MXene not only improves the material's antioxidant properties, but also enhances its chemical corrosion resistance, especially in complex environments, where the overall protective performance of the material has been significantly improved. The synergistic effect of nanoclay, graphene quantum dots (GQDs) and two-dimensional transition metal carbides / nitrides (MXene) in epoxy anhydride compositions is reflected in many aspects, including but not limited to mechanical properties, thermal stability, electrical conductivity, and chemical corrosion resistance. This synergistic effect not only significantly improves the comprehensive performance of the material, but also provides new ideas and technical means for the development of high-performance composite materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0106] Figure 1 The present invention is a preparation flow chart of an embodiment of the present invention. DETAILED DESCRIPTION
[0107] The embodiments of the present application provide an environmentally friendly stripping agent for NdFeB materials and a preparation method and a use method thereof. DETAILED DESCRIPTION
[0108] like Figure 1 As shown, the samples in the following examples were prepared using the following method:
[0109] Preparation of surfactant-modified nanoclay: dissolving a first surfactant in deionized water to prepare a first surfactant solution with a concentration of 0.5 to 2 wt %;
[0110] Adding nanoclay to the first surfactant solution to make the mass fraction of the nanoclay be 1 to 5 wt %, using ultrasound or stirring to fully disperse the nanoclay and make it completely contact with the surfactant, then washing and drying to obtain surfactant-modified nanoclay;
[0111] Preparation of surfactant-modified graphene quantum dots:
[0112] Dissolving the second surfactant in deionized water to prepare a second surfactant solution with a concentration of 1 to 3 wt %;
[0113] Dispersing graphene quantum dots into the second surfactant solution so that the mass fraction of the graphene quantum dots is 0.1 to 1 wt %;
[0114] Stirring at 60-80° C. for 1-2 hours to ensure that the surfactant molecules can be effectively adsorbed onto the surface of the graphene quantum dots, washing and drying to obtain surfactant-modified graphene quantum dots;
[0115] Preparation of surfactant-modified two-dimensional transition metal carbides / nitrides:
[0116] The third surfactant is dissolved in deionized water to prepare a third surfactant solution with a concentration of 0.5-2wt%; the two-dimensional transition metal carbide / nitride is dispersed in the third surfactant solution, and the mass fraction of the two-dimensional transition metal carbide / nitride is 0.5-2wt%.
[0117] Stir for 1 to 2 hours at 60-80°C to ensure that the surfactant molecules can be effectively adsorbed onto the surface of the two-dimensional transition metal carbide / nitride, wash and dry to obtain the surfactant-modified two-dimensional transition metal carbide / nitride.
[0118] Mix epoxy resin, modified anhydride curing agent, latent accelerator and toughening agent, stir evenly to ensure that all ingredients are fully dispersed and evenly mixed. During the stirring process, the temperature is controlled at 20°C to 80°C, the stirring speed is 500r / min to 1500r / min, the pressure is 100Pa to 101.325kPa, and the time is 1 hour to 3 hours;
[0119] The mixed composition is subjected to vacuum degassing treatment to remove bubbles generated during the mixing process. The vacuum degassing treatment time is 30 minutes to 1 hour, and the vacuum degree is -99.5KPa;
[0120] Add the thermoresponsive polymer and the photoresponsive molecule to the premixed composition and continue stirring until uniform;
[0121] Add the nanoparticles and high-performance fibers to the premixed composition and continue stirring until uniform;
[0122] Add surfactant-modified two-dimensional transition metal carbides / nitrides, surfactant-modified graphene quantum dots and surfactant-modified nanoclay into the premixed composition, and continue to stir evenly to ensure that the components are evenly distributed in the matrix.
[0123] Embodiment 1:
[0124] Epoxy resin (modified bisphenol A type): 40 parts
[0125] Modified anhydride curing agent (tung oil anhydride and 2-methyltetrahydrophthalic anhydride, mass ratio is 2:1): 50 parts
[0126] Chemical thickener (polyamide): 5 parts
[0127] Latent promoter (2-ethyl-4-methylimidazole): 1 part
[0128] Toughener (carboxyl-terminated liquid nitrile rubber): 15 parts
[0129] Surfactant-modified nanoclay (CTAB-modified montmorillonite, average particle size 30 nanometers): 3 parts
[0130] Surfactant-modified GQDs (PVA-modified, size 5 nm): 0.1 parts
[0131] Surfactant-modified MXene (CTAC-modified Ti3C2Tx): 0.5 parts
[0132] Thermoresponsive polymer (PNIPAM): 1 part
[0133] Photoresponsive molecule (azobenzene derivative): 0.5 parts
[0134] Nanoparticles (TiO2): 2 parts
[0135] High performance fiber (aramid fiber): 5 parts
[0136] Example 2: Increasing the amount of chemical thickener
[0137] Epoxy resin (modified bisphenol F type): 40 parts
[0138] Modified anhydride curing agent (tung oil anhydride and 2-methyltetrahydrophthalic anhydride, mass ratio is 1:1): 50 parts
[0139] Chemical thickener (silicone thickener): 8 parts
[0140] Latent promoter (2-ethyl-4-methylimidazole): 1 part
[0141] Toughener (carboxyl-terminated liquid nitrile rubber): 15 parts
[0142] Surfactant modified nanoclay (SDS modified bentonite, average particle size 50 nanometers): 3 parts
[0143] Surfactant-modified GQDs (PAA-modified, 7 nm): 0.2 parts
[0144] Surfactant-modified MXene (octadecylamine-modified V2CTx): 0.6 parts
[0145] Thermoresponsive polymer (PNIPAM): 1 part
[0146] Photoresponsive molecule (azobenzene derivative): 0.5 parts
[0147] Nanoparticles (Al2O3): 2 parts
[0148] High performance fiber (glass fiber): 5 parts
[0149] Example 3: Reducing the amount of high performance fibers
[0150] Epoxy resin (modified bisphenol A type): 40 parts
[0151] Modified anhydride curing agent (tung oil anhydride and 2-methyltetrahydrophthalic anhydride, mass ratio is 2:1): 50 parts
[0152] Chemical thickener (polyurethane): 5 parts
[0153] Latent promoter (2-ethyl-4-methylimidazole): 1 part
[0154] Toughener (carboxyl-terminated liquid nitrile rubber): 15 parts
[0155] Surfactant-modified nanoclay (CTAB-modified montmorillonite, average particle size 30 nanometers): 3 parts
[0156] Surfactant-modified GQDs (PVA-modified, size 5 nm): 0.1 parts
[0157] Surfactant-modified MXene (CTAC-modified Ti3C2Tx): 0.5 parts
[0158] Thermoresponsive polymer (PNIPAM): 1 part
[0159] Photoresponsive molecule (azobenzene derivative): 0.5 parts
[0160] Nanoparticles (TiO2): 2 parts
[0161] High performance fiber (aramid fiber): 2 parts
[0162] Example 4: Introducing more nanoparticles
[0163] Epoxy resin (modified bisphenol A type): 40 parts
[0164] Modified anhydride curing agent (tung oil anhydride and 2-methyltetrahydrophthalic anhydride, mass ratio is 2:1): 50 parts
[0165] Chemical thickener (polyamide): 5 parts
[0166] Latent promoter (2-ethyl-4-methylimidazole): 1 part
[0167] Toughener (carboxyl-terminated liquid nitrile rubber): 15 parts
[0168] Surfactant-modified nanoclay (CTAB-modified montmorillonite, average particle size 30 nanometers): 3 parts
[0169] Surfactant-modified GQDs (PVA-modified, size 5 nm): 0.1 parts
[0170] Surfactant-modified MXene (CTAC-modified Ti3C2Tx): 0.5 parts
[0171] Thermoresponsive polymer (PNIPAM): 1 part
[0172] Photoresponsive molecule (azobenzene derivative): 0.5 parts
[0173] Nanoparticles (TiO2): 3 parts
[0174] High performance fiber (aramid fiber): 5 parts
[0175] Comparative Example 1: No surfactant modification
[0176] Epoxy resin (modified bisphenol A type): 40 parts
[0177] Modified anhydride curing agent (tung oil anhydride and 2-methyltetrahydrophthalic anhydride, mass ratio is 2:1): 50 parts
[0178] Chemical thickener (polyamide): 5 parts
[0179] Latent promoter (2-ethyl-4-methylimidazole): 1 part
[0180] Toughener (carboxyl-terminated liquid nitrile rubber): 15 parts
[0181] Unmodified nanoclay (montmorillonite, average particle size 30 nanometers): 3 parts
[0182] Unmodified GQDs (size 5 nm): 0.1 part
[0183] Unmodified MXene (Ti3C2Tx): 0.5 parts
[0184] Thermoresponsive polymer (PNIPAM): 1 part
[0185] Photoresponsive molecule (azobenzene derivative): 0.5 parts
[0186] Nanoparticles (TiO2): 2 parts
[0187] High performance fiber (aramid fiber): 5 parts
[0188] Comparative Example 2: No addition of thermoresponsive and photoresponsive molecules
[0189] Epoxy resin (modified bisphenol A type): 40 parts
[0190] Modified anhydride curing agent (tung oil anhydride and 2-methyltetrahydrophthalic anhydride, mass ratio is 2:1): 50 parts
[0191] Chemical thickener (polyamide): 5 parts
[0192] Latent promoter (2-ethyl-4-methylimidazole): 1 part
[0193] Toughener (carboxyl-terminated liquid nitrile rubber): 15 parts
[0194] Surfactant-modified nanoclay (CTAB-modified montmorillonite, average particle size 30 nanometers): 3 parts
[0195] Surfactant-modified GQDs (PVA-modified, size 5 nm): 0.1 parts
[0196] Surfactant-modified MXene (CTAC-modified Ti3C2Tx): 0.5 parts
[0197] Nanoparticles (TiO2): 2 parts
[0198] High performance fiber (aramid fiber): 5 parts
[0199] Comparative Example 3: Nanoclay without surfactant modification
[0200] Epoxy resin (modified bisphenol A type): 40 parts
[0201] Modified anhydride curing agent (tung oil anhydride and 2-methyltetrahydrophthalic anhydride, mass ratio is 2:1): 50 parts
[0202] Chemical thickener (polyamide): 5 parts
[0203] Latent promoter (2-ethyl-4-methylimidazole): 1 part
[0204] Toughener (carboxyl-terminated liquid nitrile rubber): 15 parts
[0205] Unmodified nanoclay (montmorillonite, average particle size 30 nanometers): 3 parts
[0206] Surfactant-modified GQDs (PVA-modified, size 5 nm): 0.1 parts
[0207] Surfactant-modified MXene (CTAC-modified Ti3C2Tx): 0.5 parts
[0208] Thermoresponsive polymer (PNIPAM): 1 part
[0209] Photoresponsive molecule (azobenzene derivative): 0.5 parts
[0210] Nanoparticles (TiO2): 2 parts
[0211] High performance fiber (aramid fiber): 5 parts
[0212] Comparative Example 4: GQDs without surfactant modification
[0213] Epoxy resin (modified bisphenol A type): 40 parts
[0214] Modified anhydride curing agent (tung oil anhydride and 2-methyltetrahydrophthalic anhydride, mass ratio is 2:1): 50 parts
[0215] Chemical thickener (polyamide): 5 parts
[0216] Latent promoter (2-ethyl-4-methylimidazole): 1 part
[0217] Toughener (carboxyl-terminated liquid nitrile rubber): 15 parts
[0218] Surfactant-modified nanoclay (CTAB-modified montmorillonite, average particle size 30 nanometers): 3 parts
[0219] Unmodified GQDs (size 5 nm): 0.1 part
[0220] Surfactant-modified MXene (CTAC-modified Ti3C2Tx): 0.5 parts
[0221] Thermoresponsive polymer (PNIPAM): 1 part
[0222] Photoresponsive molecule (azobenzene derivative): 0.5 parts
[0223] Nanoparticles (TiO2): 2 parts
[0224] High performance fiber (aramid fiber): 5 parts
[0225] Comparative Example 5: MXene without surfactant modification
[0226] Epoxy resin (modified bisphenol A type): 40 parts
[0227] Modified anhydride curing agent (tung oil anhydride and 2-methyltetrahydrophthalic anhydride, mass ratio is 2:1): 50 parts
[0228] Chemical thickener (polyamide): 5 parts
[0229] Latent promoter (2-ethyl-4-methylimidazole): 1 part
[0230] Toughener (carboxyl-terminated liquid nitrile rubber): 15 parts
[0231] Surfactant-modified nanoclay (CTAB-modified montmorillonite, average particle size 30 nanometers): 3 parts
[0232] Surfactant-modified GQDs (PVA-modified, size 5 nm): 0.1 parts
[0233] Unmodified MXene (Ti3C2Tx): 0.5 parts
[0234] Thermoresponsive polymer (PNIPAM): 1 part
[0235] Photoresponsive molecule (azobenzene derivative): 0.5 parts
[0236] Nanoparticles (TiO2): 2 parts
[0237] High performance fiber (aramid fiber): 5 parts
[0238] Experimental example:
[0239] Strength tests and electromagnetic shielding tests were performed on Examples 1-4 and Comparative Examples 1-5. The electromagnetic shielding tests included: test frequency range: 1 GHz to 18 GHz, sample thickness: 2 mm, test equipment: vector network analyzer (VNA), shielding effectiveness test system, test standard: GB / T 6113.1-2013 "Specification for Radio Disturbance and Immunity Measurement Equipment and Measurement Methods", and the experimental results are shown in Table 1:
[0240] Table 1. Experimental data of Examples 1-4 and Comparative Examples 1-2
[0241]
[0242] From this we can see that:
[0243] Effect of surfactant modification: Examples 1 to 4 all used surfactant-modified nanoclay, GQDs and MXene, and their tensile strength, tensile modulus, elongation at break, glass transition temperature (Tg) and electromagnetic shielding effectiveness were significantly better than those of Comparative Examples 1 to 5, indicating that surfactant modification significantly improved the comprehensive performance of the material.
[0244] Effects of each nanomaterial: By comparing Comparative Examples 3, 4 and 5, it can be found that each nanomaterial (nanoclay, GQDs, MXene) plays an important role in improving the performance of the material after surfactant modification. The lack of any surfactant-modified nanomaterial will lead to a decrease in material performance, especially a significant decrease in electromagnetic shielding effectiveness.
[0245] Role of thermoresponsive and photoresponsive molecules: Examples 1 to 4 all added thermoresponsive polymers (PNIPAM) and photoresponsive molecules (azobenzene derivatives), while Comparative Examples 2, 4, and 5 did not add these ingredients. The results showed that the examples had significant improvements in electromagnetic shielding effectiveness, indicating that these responsive molecules are very important for optimizing the functional properties of the material.
[0246] Adjustment of the ratio of chemical thickeners, nanoparticles and high-performance fibers: By changing the ratio of these components (such as increasing the amount of chemical thickeners in Example 2, reducing the amount of high-performance fibers in Example 3, and increasing the amount of nanoparticles in Example 4), the specific performance indicators of the material can be flexibly adjusted to meet the needs of different application scenarios.
[0247] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.
[0248] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A chemically thickened epoxy anhydride composition, characterized in that: It is composed of the following components in parts by weight: Epoxy resin: 35-45 parts; Modified anhydride curing agent: 40-55 parts; Chemical thickener: 3-8 parts; Latent promoter: 0.5-2 parts; Toughening agent: 5-20 parts; Surfactant-modified nanoclay: 0.5-5 parts; Surfactant-modified graphene quantum dots: 0.01-0.5 parts; Surfactant-modified two-dimensional transition metal carbide / nitride: 0.1-1 part; Thermal responsive polymer: 0.1-2 parts; Photoresponsive molecules: 0.05 to 1 part; Nanoparticles: 0.5-3 parts; High performance fiber: 0-10 parts; Wherein, the modified anhydride curing agent comprises a compound having a structure of Formula 1: R-(CO)n-(OCH2CH2)m-OH Formula 1 Wherein, R is a C3-C6 alkyl group or a branched alkyl group, n is an integer from 1 to 10, and m is an integer from 10 to 40.
2. The epoxy anhydride composition according to claim 1, characterized in that: The epoxy resin is selected from modified bisphenol A epoxy resin and modified bisphenol F epoxy resin; The modified anhydride curing agent is a mixture of tung oil anhydride and 2-methyltetrahydrophthalic anhydride, and the mass ratio of the tung oil anhydride to the 2-methyltetrahydrophthalic anhydride is 1:1 to 3:1; The chemical thickener is selected from one or more of polyamide, polyurethane and silicone thickeners.
3. The epoxy anhydride composition according to claim 1, characterized in that: The latent promoter is 2-ethyl-4-methylimidazole; The toughening agent is carboxyl-terminated liquid nitrile rubber.
4. The epoxy anhydride composition according to claim 1, characterized in that: The surfactant-modified nanoclay is nanoclay modified with a first surfactant; Wherein, the first surfactant is one of hexadecyltrimethylammonium bromide and sodium dodecyl sulfate; The average particle size of the nanoclay is 10 to 100 nanometers; The nano clay is one or both of montmorillonite and bentonite.
5. The epoxy anhydride composition according to claim 1, characterized in that: The nanoparticles are selected from titanium dioxide and aluminum oxide; The high-performance fiber is selected from aramid fiber and glass fiber.
6. The epoxy anhydride composition according to claim 1, characterized in that: The thermoresponsive polymer is poly(N-isopropylacrylamide); The photoresponsive molecule is a type of azobenzene derivative.
7. The epoxy anhydride composition according to claim 1, characterized in that: The surfactant-modified graphene quantum dots are graphene quantum dots modified with a second surfactant; Wherein, the second surfactant is one of polyvinyl alcohol and polyacrylic acid; The size of the graphene quantum dots ranges from 1 to 10 nanometers.
8. The epoxy anhydride composition according to claim 1, characterized in that: The surfactant-modified two-dimensional transition metal carbide / nitride is a two-dimensional transition metal carbide / nitride modified by a third surfactant; Wherein, the third surfactant is one or both of hexadecyltrimethylammonium chloride and octadecylamine; The two-dimensional transition metal carbide / nitride is one or more of Ti3C2Tx, V2CTx, and Nb2CTx.
9. A method for preparing the epoxy anhydride composition according to claim 1, characterized in that: The following steps are involved: Preparation of surfactant-modified two-dimensional transition metal carbides / nitrides, surfactant-modified graphene quantum dots, and surfactant-modified nanoclays; Mix the epoxy resin, modified anhydride curing agent, latent accelerator and toughening agent, and stir evenly to ensure that all ingredients are fully dispersed and evenly mixed; The mixed composition is subjected to vacuum degassing treatment to remove bubbles generated during the mixing process. The vacuum degassing treatment time is 30 minutes to 1 hour, and the vacuum degree is -99.5KPa; Add the thermoresponsive polymer and the photoresponsive molecule to the premixed composition and continue stirring until uniform; Add the nanoparticles and high-performance fibers to the premixed composition and continue stirring until uniform; The surfactant-modified two-dimensional transition metal carbide / nitride, the surfactant-modified graphene quantum dots and the surfactant-modified nanoclay are added to the premixed composition, and the mixture is stirred evenly to ensure that the components are evenly distributed in the matrix.
10. The preparation method according to claim 9, characterized in that: The preparation of surfactant-modified two-dimensional transition metal carbides / nitrides, surfactant-modified graphene quantum dots and surfactant-modified nanoclays comprises: Preparation of the surfactant-modified nanoclay: dissolving a first surfactant in deionized water to prepare a first surfactant solution with a concentration of 0.5 to 2 wt %; Adding nanoclay to the first surfactant solution to make the mass fraction of the nanoclay be 1 to 5 wt %, using ultrasound or stirring to fully disperse the nanoclay and make it completely contact with the surfactant, then washing and drying to obtain the surfactant-modified nanoclay; Preparation of the surfactant-modified graphene quantum dots: Dissolving the second surfactant in deionized water to prepare a second surfactant solution with a concentration of 1 to 3 wt %; Dispersing graphene quantum dots into the second surfactant solution so that the mass fraction of the graphene quantum dots is 0.1 to 1 wt %; stirring at 60-80° C. for 1-2 hours to ensure that the surfactant molecules can be effectively adsorbed onto the surface of the graphene quantum dots, washing and drying to obtain the surfactant-modified graphene quantum dots; Preparation of surfactant-modified two-dimensional transition metal carbides / nitrides: The third surfactant is dissolved in deionized water to prepare a third surfactant solution with a concentration of 0.5-2wt%; the two-dimensional transition metal carbide / nitride is dispersed in the third surfactant solution, and the mass fraction of the two-dimensional transition metal carbide / nitride is 0.5-2wt%. The mixture is stirred at 60-80° C. for 1-2 hours to ensure that the surfactant molecules can be effectively adsorbed onto the surface of the two-dimensional transition metal carbide / nitride, and then washed and dried to obtain the two-dimensional transition metal carbide / nitride modified by the surfactant.
Citation Information
Patent Citations
Carbon composite comprising MXene and graphene foam, method for manufacturing the same and use thereof
KR102108832B1
Cited By
Soil heavy metal pollution remediation method based on nanometer materials
CN120460455A
Epoxy resin composition and preparation method thereof, prepreg and preparation method thereof
CN120737546A